A phase I study to evaluate the effect of high-dose carbidopa on levodopa pharmacokinetics - Hayashi, Akane; Hosomi, Atsushi; Kihara, Shinsaku; Nishi, Masato; Torisawa, Saori; Ouchi, Yoshiumi; Takada, Hidenori; Enokizono, Junichi (Frontiers in Pharmacology, 2025)
Levodopa is the gold standard treatment for Parkinson’s disease. However, a high unmet medical need exists for longer-lasting oral levodopa formulations to achieve sustained motor improvement with reduced risk of the effect wearing off. In our previous non-clinical studies using rats, more than 3-fold prolongation of the levodopa half-life was achieved when it was combined with a high carbidopa dose. This study aimed to evaluate the effects of high-dose carbidopa on the pharmacokinetics of levodopa. A phase I study was performed to examine the effects of a combination of levodopa, carbidopa, and entacapone in healthy male volunteers. Levodopa and entacapone doses were set at approved dose levels. The carbidopa dose ranged from the approved 10 mg–600 mg. In addition to plasma concentrations of levodopa, those of the metabolites were also determined to evaluate their inhibitory effects on levodopa-metabolizing enzymes. The plasma concentrations of levodopa and its metabolites were monitored by liquid chromatography-tandem mass spectrometry up to 24 h after administration. The observed adverse effects were mild, and all participants completed the study. At higher carbidopa doses, the area under the levodopa plasma concentration-time curve increased by approximately 2-fold, and the half-life of levodopa was slightly prolonged by < 1.4-fold. These changes were much smaller than those observed in rats. The ratios of levodopa metabolites suggested that dopa deoxycarboxylase inhibition was saturated at a carbidopa dose of 300 mg. In conclusion, higher carbidopa doses are tolerable, and the effect of carbidopa on levodopa half-life is limited.Clinical trial registrationhttps://jrct.mhlw.go.jp/en-latest-detail/jRCT2051200104, registry number jRCT2051200104.